Struggle for influence between Russia, Turkey and Iran on Central Asian Republics - Muslu, Hüseyin (My University, 2000)
After the disintegration of Soviet Union; with their rich natural resources and geostrategic importance Central Asian states appeared at the focus of the international society. It is natural that neighboring states, regional powers and transnational corporations should all take a very keen interest in Central Asia. All of the major states, including Russian Republic, Turkey, Iran, Saudi Arabia, the US, the EU, Pakistan, China, Japan and Israel have taken an active interest in recent developments in Central Asia. Turkey, Russia and Iran, as regional powers, locked in a very rivalry to gain competitive advantage against each other in the region. Initiated to fill this political vacuum, Turkey and Iran seek to establish or redefine long-standing ties based on ethnicity, language, culture, religion, geography, and history; while Russia was showing open assertiveness to preserve its vital interests in this part of 'near abroad'. Short period after disintegration Russia has succeeded in defending its position as the dominant external power in Central Asia and has effectively limited the potential for other neighboring countries, such as Turkey and Iran. But Russian influence has not been so pervasive and restrictive as to exclude these other neighboring countries from Cen-tral Asia. In this competition, in economic, political and security concerns Russia seemed to be ahead. But in cultural areas Turkey managed to develop powerful ties. In economic areas Turkish private sector also seems to be active in the region. Iran, because of its geographic proximity, succeeded in developing transportation and gas pipeline infrastructures.

Sovyetler Birliği'nin dağılmasıyla birlikte, zengin doğal kaynaklara ve jeostratejik konuma sahip Orta Asya Ülkeleri bir anda uluslararası toplumun ilgi odağı oldu. Komşu ülkelerin, bölgesel güçlerin ve çok uluslu şirketlerin bu ülkeler ilgi duyması doğal bir gelişmeydi. İçlerinde Rusya Federasyonu, Türkiye, İran, Suudi Arabistan, Amerika Birleşik Devletleri, Avrupa Birliği Ülkeleri, Pakistan, Çin, Japonya ve İsrail' in de bulunduğu bütün büyük devletler bölgedeki gelişmeleri yakından takip ediyorlar. Bölgesel güç ülkeleri olarak Türkiye, Rusya ve İran bir birlerine karşı bölgede belli avantajlar yakalamak için bir rekabete giriştiler. Türkiye ve İran oluşan bu politik boşluğu doldurmak için, ortak etnik köken, dil, kültür, din, coğrafya ve tarihe dayandırdıkları bir rekabete girişlerken, Rusya, 'yakın çevre'deki hayati çıkarlarını korumak için varlığını olduğunca göstermeye çalışıyordu. Sovyetler Birliği'nin çözülmesinden kısa zaman sonra Rusya, Orta Asya'da birinci güç olduğunu göstererek Türkiye ve Iran gibi komşu ve bölgesel güçlerin etkinlik potansiyellerini sınırlandırdı. Fakat Rusya'nın etkisi diğer ülkelerin etkinlikte bulunmasını tamamen engelleyecek kadar nüfuz edici değildir. Bu rekabette ekonomik, politik ve güvenlik konularında Rusya'nın başat gücü tartışmasız bir şekilde kendini gösterdi. Fakat kültürel alanda Türkiye uzun vadeli ve güçlü bağlar geliştirmeyi başardı. Ekonomik alanda ise Türk özel sektörünün etkin olduğunu görüyoruz. Iran coğrafi yakınlığın verdiği avantajlarla taşıma ve gaz boru hatları konusunda belli mesafeler aldı.
Keywords: İran-Uluslararası İlişkiler-Orta Asya Cumhuriyetleri; Rusya-Uluslararası İlişkiler-Orta Asya Cumhuriyetleri; Türkiye-Uluslararası İlişkiler-Orta Asya Cumhuriyetleri